Network routing by mobile agents for image retrieval using fuzzy genetic algorithms - Selamat, Ali; Selamat, Mohd. Hafiz; Bakri, Aryati; Sulaiman, Sarina; Selamat, Fatimah @ Salwa; Mohd. Daud, Mariah (Faculty of Computer Science and Information System, 2005)
Mobile agents often have a task to collect data from several predefined sites. This should be done in an efficient way by minimizing the elapsed time. Usually these agents only know the list of sites but not the distance s between them. This research proposes a method to minimize a network routing time taken by the mobile agents using genetic algorithm (GA) to collect query datasets from different hosts from the World Wide Web. The mobile agents repeat traveling over short routes and avoid longer ones. The GA will be used to select the best routes that will be used by mobile agents to retrieve query datasets in a very short time. Specifically, the performance of mobile agent in obtaining a query result from the remote hosts using extended hierarchical query retrieval (EHQR) approach is proposed. It is based on a hierarchical and a parallel dispatching of mobile agents to the remote servers in order to retrieve the query results. The new dispatching algorithms for mobile agents to be dispatched to various sited have been developed such as an itinerary query retrieval approach (IQR), a parallel query retrieval approach (PQR), a serial query retrieval approach (SQR) a shuttle query retrieval approach (SHQR), a hierarchical query retrieval approach (HQR) and the EHQR approach Experimental results show that the proposed approach reduces the number of mobile agents and also improve the total time taken to retrieve the query results compared with other approaches.